Biome evolution and biogeographical change through time - Christine Bacon (Frontiers of Biogeography)
Keystone plant groups can be used to infer the evolution of biomes and biogeographical change of communities and taxa. In this thesis I investigated whether lineages in Trachycarpeae palms could be used to track different forest types through time and whether change in biome or biogeographic region had an effect on species diversification. These questions were approached using genetic data integrated with fossil record, species distribution, and speciation models. Although the three chapters of my thesis had additional foci outside of the main goal of inferring biogeographic change and diversification through time, they come together to paint a clear picture of how fine-scale and interdisciplinary studies can lead to more robust hypothesis testing and conclusions. I found that outside of tracking tropical forests through time, palms are useful for understanding island biogeography and the formation of other types of biomes.